P–490 Recurrent pregnancy loss acts as a posttraumatic stress event in both women and men. (6th August 2021) - Kuhlmann, E; Voss, P; Schick, M; Ditzen, B; Langer, L; Strowitzki, T; Wischmann, T; Kuon, R J
Abstract: Study question: What are the psychological impacts of recurrent pregnancy loss (RPL) on men and women and their interdependencies? Summary answer: Women show higher psychological risks than men, except for lack of social support. Avoidance behaviour of men correlates with higher posttraumatic stress of their partner. What is known already: About 1–3% of all couples trying to conceive are affected by RPL. The loss of the unborn child can be the most traumatic experience in a woman's life and is associated with significant psychological distress besides the instant grief. RPL can also be stressful for the partner, even though being at a lower risk for psychiatric morbidities. The man's gender role expects him to support and not to show weakness which may result in a suppression of his feelings and a disenfranchised grief. Study design, size, duration: Cross-sectional study. All women and men referred to the special unit for RPL between March 2019 and October 2020 were asked to participate voluntarily with a total sample size of 105 couples and 17 women. Exclusion criteria were less than two pregnancy losses, inadequate knowledge of the German language and incomplete data. Participants/materials, setting, methods: Couples were invited to fill out a questionnaire package estimating their psychological risks (e.g. posttraumatic stress disorder, anxiety, depression, perceived social support) and coping strategies with established instruments. Clinical history was obtained from medical records. Couple data were analysed with the Actor Partner Interdependence Model, taking the couple as the unit of analysis. Main results and the role of chance: The response rate was 82.3%. The following psychological risks were measured among women versus men: posttraumatic stress disorder (PTSD): 13.7% versus 3.9% (p = 0.017); anxiety: 50.4% versus 17.3% (p < 0.001), depression: 48.1% versus 14.4% (p < 0.001), lack of social support: 32.5% versus 32.7% (N.S.). A risk in at least one category showed 68.9% of women versus 44.8% of men (p < 0.001), with those at higher risk indicating a lower satisfaction with their partnership (p < 0.001) and higher impairment of their sexual life (p < 0.001). Neither total number of pregnancy losses nor time gap since last pregnancy loss showed relevant correlations with psychological risks. For women, number of curettages, controlled for the number of pregnancy losses, correlates with the severity of posttraumatic stress (p < 0.05). Higher levels of anxiety, depression and a lack of social support in women correlated positively with posttraumatic stress in their partners. The coping strategy "trivialization and wishful thinking" as well as the subscale "avoidance" of the Impact-of-Event-Scale (self-report questionnaire measuring posttraumatic stress) of men was correlated with more severe posttraumatic stress in their female partners (both p < 0.05). Limitations, reasons for caution: The data show only correlations between the measured variables, as cross-sectional studies are not suitable to analyse causal relationships. The sample was obtained in a special unit for RPL at a university hospital, so the findings may not be generalizable to all couples with RPL. Wider implications of the findings: Screening psychological risks in couples with RPL may be reasonable considering the high risks in both sexes and the extent of PTSD diagnoses in women, their interdependencies and the potential risk of chronification. Professionals should encourage affected couples to support each other and provide targeted information on mental health services. Trial registration number: DRKS 00014965